2017
DOI: 10.24323/akademik-gida.333632
|View full text |Cite
|
Sign up to set email alerts
|

Narın Farklı Bölümlerinin Polifenol İçeriği, Antioksidan ve Antibakteriyel Aktivitesi Üzerine Ekstraksiyon Çözgenlerinin Etkisi

Abstract: Polyphenols in rinds, membranes and seeds of pomegranates were extracted with acetone, acetone:water (70:30, v:v), methanol, ethanol and water for 12 h at 4C. Gallic acid, punicalin, -punicalagin, -punicalagin and ellagic acid derivatives (EAD) were identified in rind and membrane, while only EAD were identified in seed by HPLC. The rind and membrane contained exceptionally high amounts of polyphenols. Strong correlations were found between antioxidant activity (AOA) and total polyphenol content (TPC) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our data is in contradiction with Cha et al findings who observed that the decreasing order of TPC and TFC in Korean Opuntia humifusa fruit was 80% ethanol > 80% methanol and 80% acetone (p > 0.05) whereas they are in [31,41,42]. Although alcoholic aqueous mixtures have been confirmed to be very effective for the extraction of high polyphenols and flavonoids, some recent studies proved that different combinations of acetone and water (50-80%) exhibited the highest values of TPC and/or TFC sometimes without any significance difference with their homologous alcoholic water mixtures [42][43][44][45][46][47][48].…”
Section: Tpc and Tfcmentioning
confidence: 94%
“…Our data is in contradiction with Cha et al findings who observed that the decreasing order of TPC and TFC in Korean Opuntia humifusa fruit was 80% ethanol > 80% methanol and 80% acetone (p > 0.05) whereas they are in [31,41,42]. Although alcoholic aqueous mixtures have been confirmed to be very effective for the extraction of high polyphenols and flavonoids, some recent studies proved that different combinations of acetone and water (50-80%) exhibited the highest values of TPC and/or TFC sometimes without any significance difference with their homologous alcoholic water mixtures [42][43][44][45][46][47][48].…”
Section: Tpc and Tfcmentioning
confidence: 94%
“…Hence, these compounds could act as natural additives to food preservation and quality improvement, providing an alternative to synthetic antimicrobial and antioxidant use (Hygreeva et al, 2014; Karre et al, 2013; Oswell et al, 2018). Antibacterial effects of pomegranate peel extracts have been described in several studies (Sharayei et al, 2020; Singh et al, 2019), such as antimicrobial activities against Gram‐negative bacteria ( Escherichia coli , Enterobacter aerogenes and Pseudomonas aeruginosa ) and Gram‐positive bacteria ( Staphylococcus aureus , Listeria monocytogenes , Bacillus subtilis , Bacillus cereus and Enterococcus faecalis ), as well as against yeasts and fungi ( Aspergillus niger, Candida albicans , Fusarium oxysporum ) (Balaban, Koc, Sar, & Yesilcimen Akbas, 2021; Fawole et al, 2012; Malviya et al, 2014; Türkyılmaz et al, 2017). Besides, Bakkiyaraj et al (2013) and Balaban, Koc, Sar, and Akbas (2021) described pomegranate antibiofilm formation of S. aureus, E. coli, C. albicans, B. subtilis, B. cereus and E. faecalis .…”
Section: Introductionmentioning
confidence: 99%